Legal Protection of Registered Brand Holders (A case study of the infringement of the Kaso brand light steel) - Dionisius Purwo Sudarsono (Fakultas Hukum, Universitas Warmadewa, 2022)
For companies that manufacture good products with registered trademarks that are known by the public, they definitely have good market shares. It is undeniable that many companies practice unfair business competition by imitating or using other parties’ registered trademarks to market their products. The objective of this research is to obtain a legal basis for trademark rights in Indonesian positive law and the implementation of legal protection for the holder of registered trademark of lightweight steel products under brand of